Pengaruh Mikroorganisme Lokal (MOL) Rebung Bambu dan Lama Perendaman terhadap Pertumbuhan Mucuna bracteata - Indra Setiawan Rambe; Bayu Pratomo; Rama Riana Sitinjak; Abednego Suranta Karosekali; Laura Juita Pinem; Edy Fachrial (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Rambe IS, Pratomo B, Sitinjak RR, Karosekali AS, Pinem LJ, Fachrial E. 2020. The effect of bamboo shoots as local microorganisms (MOL) and soaking time on the growth of mucuna bracteata. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The Effect of Bamboo Shoots as Local Microorganisms (MOL) and Soaking Time on The Growth of Mucuna bracteata. The research is aimed at obtaining the concentration of microorganism local bamboo shoots and long soaking the right to increase the growth of plants Mucuna bracteata. The study used an experimental method with a 2 factorial randomized block design (RBD). The first factor is the MOL concentration of the bamboo shoots which consist of 4 level that is: Control (R0), 100 ml/l (R1), 150 ml/l (R2), 200 ml/l (R3) and a factor of two is long immersion which consists of 4 level that is: Control (M0), 15 minutes (M1), 30 minutes (M2), 45 minutes (M3). The data were analyzed using (Analysis of Variance) with a significant 5% and followed by The DMRT (Duncan Multiple Range Test) with a significant 5% using SAS software version 9.3.1. Based on the results of data analysis, the results showed that the effect of local microorganism concentration (MOL) of bamboo shoots on Mucuna bracteata plants had a significant effect on tendril length at a concentration of 150 ml/l (R2) at the age of 4-5 MST and a concentration of 200 ml/l (R3) in age 6 MST, and root shoot ratio at a concentration of 150 ml/l (R2), but did not significantly affect the number of leaves, fresh and dry weight of shoots, fresh and dry weight of roots, number of root nodules, and root length. Soaking time and interaction had no significant effect on the number of leaves, tendrils length, weight of fresh and dry shoot, fresh and dry weight of root, root nodule number, root length, and the ratio of root header.